Understanding telephone electronics - Bigelow, Stephen J. (Newnes, 2001)
Provides comprehensive coverage of telephone system functions and the role of the Internet in telephony Updates encompass the trends and advances of the booming telecommunications field, with new chapters on fiber optic technology and the Internet .